Long-Term Effects of Chronic Khat Use: Impaired Inhibitory Control - Colzato, Lorenza S.; Ruiz, Manuel; Van Den Wildenberg, Wery P.; Bajo, Maria Teresa; Hommel, Bernhard (Frontiers in Psychology, 2011)
So far no studies have systematically looked into the cognitive consequences of khat use. This study compared the ability to inhibit and execute behavioral responses in adult khat users and khat-free controls, matched in terms of age, race, gender distribution, level of intelligence, and alcohol, and cannabis consumption. Response inhibition and response execution were measured by a stop-signal paradigm. Results show that users and non-users are comparable in terms of response execution but users need significantly more time to inhibit responses to stop signals than non-users.